Report on the Economic Survey of Madras City - Planning Commission (Planning Commission, 1954)
The Research Unit for the, economic survey of Madras city sponsored by the Research Programmes Committee of the Planning Commission was formed on die 15lh April 1954 with the Professor and Head of the Department of Economics, University of Madras as Honorary Director. At the outset sanction was accorded for the appointment of one Deputy Director. Three Supervisors, Two Tabulators. Eight Investigators, One Clerk-cum-Typist and One Peon. In July 1955 the strength of the staff was increased by the appointment of two more Investigators in order to cope with the additional field work relating to a subsidiary survey of Fertility and Family Planning. The Unit started functioning with less than the sanctioned strength in the first few months and the full complement was in position from September 1954. During the period of more than three and a half years of its tenure, certain changes had to be made in the personnel on account of members leaving the Unit and consequential promotions, the details of which could be seen in Appendix I. The University of Madras was pleased to provide adequate accommodation, electricity and other facilities free of charge.
Planning Commission Research Programmes Committee
Planning Commission